The Process Of Muja Sumbang Ceremony Among Kaharingan Hindus In Papar Pujung Village, West Lahei Sub-District, North Barito Regency - Malia; Mitro; Megawati Megawati (IAHN-TP Palangka Raya, 2024)
Muja Sumbang comes from the Dayak language of Dusun Malang in Lahei Barat regency, North Barito district. Muja Sumbang is composed of two words,